Kobieta między snem a jawą w wybranych tekstach Hansa Christiana Andersena .......... 99 - Kocha, Sandra Magdalena (Sny kobiet, sny o kobietach – od romantyzmu do Młodej Polski, 2020)
A WOMAN BETWEEN SLEEPING AND WAKING IN SELECTED TEXTS BY HANS CHRISTIAN ANDERSENThe purpose of the article is to show how thanks to oneiric motifs can be an in-depth characterization of women depicted in fairy tales and stories by Hans Christian Andersen. An important matter is the times in which he wrote – namely, romanticism. At that time, women were presented as seductive lovers on the one hand, and as innocent and pure angels on the other. The models of the female psyche, i.e. the Amazon, Hetera, Mediatressand Mother, separated by Toni Wolff, allow us to assign Andersen’s works to individual types.